Rose - Smith, Martin Cruz, 1942- (New York : Ballantine Books, 2000)
The year is 1872. The place is Wigan, England, a coal town where rich mine owners live lavishly alongside miners no better than slaves. Into this dark, complicated world comes Jonathan Blair, who has accepted a commission to find a missing man. When he begins his search every road leads back to one woman, a haughty, vixenish pit girl named Rose. With her fiery hair and skirts pinned up over trousers, she cares nothing for a society that calls her unnatural, scandalous, erotic. As Rose and Blair circle one another, first warily, then with the heat of mutual desire, Blair loses his balance. And the lull induced by Rose's sensual touch leaves him unprepared for the bizarre, soul-scorching truth.
"This edition published by arrangement with Random House, Inc."
Keywords: Man-woman relationships -- England -- Lancashire -- Fiction; Women coal miners -- England -- Lancashire -- Fiction; Mining engineers -- England -- Lancashire -- Fiction; Missing persons -- England -- Lancashire -- Fiction; Lancashire (England) -- History -- Fiction; Historical fiction; Love stories